Liquid phase nonpoint source pollution dispersion through conveyance structures to sustainable urban drainage system within different land covers - Moruzzi, Rodrigo B. [UNESP]; de Lima, João L.M.P.; Abrantes, João R.C.B.; Silveira, Alexandre (Elsevier, 2020)
Liquid-phase nonpoint source pollution dispersion and removal on sustainable urban drainage systems (SUDS) is an important issue for urban pollution mitigation which remains a challenge, as current researches mostly focus on pollutants removal by settling. Nevertheless, most of liquid-phase pollutants behave as dissolved substances on overland flow and, therefore, they cannot be trapped, but uptake by biological mechanisms and adsorbed by green infrastructure media. Hence, dispersion of dissolved pollutant is of great importance for liquid-phase pollution removal, as it also increases contact with underlying media in the SUDS. This paper addresses the liquid-phase pollutant dispersion on conveyance structures within different materials, using experimental and modelling analysis. Hydrodynamic dispersion and flow velocity were analysed separately, or conjoint, using dispersivity, as it is a key factor for porous solute transport and removal. Therefore, the effect of different covers on pavements draining to, or as part of, SUDS with very shallow runoff was investigated. Four scenarios were performed in triplicate to measure the flow velocity and the conservative solute transport across longitudinal section of flume (experimental indoors self-contained setup) using electrolyte tracer under different flow discharges (32–1813 ml s−1) with 0.8, 4.4 and 13.2% slopes. For one scenario, free water flow on a smooth surface was performed and results were used as control. For the three remaining scenarios: sand roughness, stone and synthetic grass covers were investigated. The ratio of the dispersion coefficient and flow velocity (i.e. dispersivity factor) was also determined and compared with control. Finally, data were analysed considering flow regimes, using the dimensionless Reynolds and Froude numbers. Results showed that surface covers caused reduction in the flow velocity, from 1.2 to 7.7 fold. However, dispersivity factor can be increased from 3 to nearly 10 orders of magnitude for the three scenarios, compared to control, due to the dual effect on hydrodynamic dispersion coefficient and flow velocity. Results here presented should be helpful to better understand dissolved non-point source pollution dispersion and how different land covers can effect pollutant removal.
Keywords: Hydrodynamic dispersion; Nonpoint pollution; Overland flow; Solute transport; Urban drainage